Pemberian Asi Eksklusif di Wilayah Kerja Puskesmas Tapung Perawatan Tahun 2015 - Rizki Rahmawati Lestari (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
Exclusive Breastfeeding coverage in various regions of Indonesia is still far from the National target. This study aims to determine the factors associated with exclusive breastfeeding in the Work Area Puskesmas Tapung Treatment District Kampar Riau Province with a cross-sectional design. The research was conducted on June 12-29, 2015. The variables in this study include the support of health workers, mother's knowledge, husband support, mother's work, mother's education, mother's age and maternal age of the pregnancy. Sampling by systematic random sampling (n = 120). Data were analyzed using Logistic Regression Test. The results of this study indicate that the variables associated with exclusive breastfeeding are husband support (POR: 8,219 95% CI = 2,848-23,719), maternal occupations (POR: 5.188 95% CI = 1,264-21,301), and maternal education (POR: 3.785 95% CI = 1,110-12,904). Suggestions for the Puskesmas to provide communication, information, education about exclusive breastfeeding to married couples.